2019
DOI: 10.1109/access.2019.2941287
|View full text |Cite
|
Sign up to set email alerts
|

Singularity Analysis of Cutting Force and Vibration for Tool Condition Monitoring in Milling

Abstract: Tool wear is inevitable in manufacturing and affects the surface quality and geometric tolerance significantly. A robust and efficient tool condition monitoring (TCM) system is needed to maximize tool life, ensure work-piece quality, and benefit the cost control of manufacturers. This paper presents a systematic singularity analysis approach of cutting force and vibrations for feature extraction of TCM in milling. The singularity of sensory signals is estimated by Holder Exponents (HE), which are determined by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(14 citation statements)
references
References 42 publications
0
14
0
Order By: Relevance
“…The selection of wavelet basis functions is critical for the singularity analysis of sensory signals. Zhou et al [24], [25] found the wavelet basis with two vanishing moments were the most appropriate wavelet to detect the singularities in the vibration signals of the milling process. And Gaussian wavelet can ensure the continuity of the modulus maxima line [18].…”
Section: Results and Discussion A He Estimation Proceduresmentioning
confidence: 99%
See 2 more Smart Citations
“…The selection of wavelet basis functions is critical for the singularity analysis of sensory signals. Zhou et al [24], [25] found the wavelet basis with two vanishing moments were the most appropriate wavelet to detect the singularities in the vibration signals of the milling process. And Gaussian wavelet can ensure the continuity of the modulus maxima line [18].…”
Section: Results and Discussion A He Estimation Proceduresmentioning
confidence: 99%
“…While calculating WTMMs, the samples dominated by noise would result in a large number of pseudo-WTMMs. And these pseudo-WTMMs would increase remarkably as the s reduces, this characteristic can be employed to remove these contaminations as a de-noising method [25].…”
Section: B Holder Exponentmentioning
confidence: 99%
See 1 more Smart Citation
“…Saini and Yu et al [3,4] sudied the influence of tool cutting performance on vibration problems for different materials. Zhou et al [5] presented an approach for systematic singularity analysis of cutting force and vibration in feature extraction. Li et al [6] developed a single-degree of freedom chatter model by taking the nonlinear hysteretic and exciting force into account.…”
Section: Introductionmentioning
confidence: 99%
“…Cutting tool plays a vital role in the cutting process, whose abnormal changes directly affect the machining accuracy and workpiece surface quality [1]- [3]. Thus, monitoring the tool cutting conditions, such as cutting force [4], torque [5], vibration [6], and temperature [7], is becoming particularly important, and thus has recently aroused great concerns from both academia and industry.…”
Section: Introductionmentioning
confidence: 99%